An ultrasound assisted, ionic liquid-molecular iodine synergy driven efficient green synthesis of pyrrolobenzodiazepine-triazole hybrids as potential anticancer agents - Saquib, Mohammad; Ahamad, Shakir; Khan, Mohammad Faheem; Khan, Mohammad Imran; Hussain, Mohd Kamil (Frontiers in Pharmacology, 2023)
Herein, we report an efficient and eco-friendly, ultrasound assisted synthetic strategy for the construction of diversified pyrrolobenzodiazepine-triazole hybrids, which are potentially pharmaceutically important scaffolds, via a domino reaction involving intermolecular electrophilic substitution followed by intramolecular Huisgen 1,3-dipolar azide-alkyne cycloaddition. The USP of the reported protocol is the use of benign and inexpensive, recyclable molecular iodine-ionic liquid synergistic catalytic system cum reaction media for achieving the synthesis. The other salient features of this method are the use of mild reaction conditions, high yield and atom economy, operational simplicity, broad substrate scope and easy workup and purification. All the synthesized compounds were evaluated for in vitro anti-proliferative activity against various cancer cell lines. From among the synthesized title compounds, 9,9-dimethyl-8-phenyl-9H-benzo[b]pyrrolo[1,2-d][1,2,3]triazolo[5,1-g][1,4]diazepine (7) was found most to be the most active compound exhibiting IC50 value of 6.60, 5.45, 7.85, 11.21, 12.24, 10.12, and 11.32 µM against MCF-7, MDA-MB-231, HeLa, SKOV-3, A549, HCT-116 and DLD-1 cell lines, respectively. Further the compounds were found to be nontoxic against normal human embryonic kidney (HEK-293) cell line.